(untitled) (Marketing Journal, 2025)
This article analyzes the importance of applying digital technologies in the fields of medical education and healthcare educational institutions, as well as their role in organizing the educational process in an effective and interactive manner. The study highlights the main principles, methods, and strategies developed for the systematic and efficient implementation of digital technologies in the learning process. In addition, issues such as clearly defining goals and objectives, studying students’ needs, selecting appropriate technologies and organizing their integration, monitoring and evaluating the educational process, as well as ensuring its continuous development and renewal, are considered. The article scientifically analyzes the advantages of introd ucing modern digital technologies and their importance in improving the quality of medical education.